Clot properties and cardiovascular disease - Bridge, Katherine I.; Philippou, Helen; Ariëns, Robert A. S. (Thrombosis and Haemostasis, 2014)
Fibrinogen is cleaved by thrombin to fibrin, which provides the blood clot with its essential structural backbone. As an acute phase protein, the plasma levels of fibrinogen are increased in response to inflammatory conditions. In addition to fibrinogen levels, fibrin clot structure is altered by a number of factors. These include thrombin levels, treatment with common cardiovascular medications, such as aspirin, anticoagulants, statins and fibrates, as well as metabolic disease states such as diabetes mellitus and hyperhomocysteinaemia. In vitro studies of fibrin clot structure can provide information regarding fibre density, clot porosity, the mechanical strength of fibres and fibrinolysis. A change in fibrin clot structure, to a denser clot with smaller pores which is more resistant to lysis, is strongly associated with cardiovascular disease. This pathological change is present in patients with arterial as well as venous diseases, and is also found in a moderate form in relatives of patients with cardiovascular disease. Pharmacological therapies, aimed at both the treatment and prophylaxis of cardiovascular disease, appear to result in positive changes to the fibrin clot structure. As such, therapies aimed at ‘normalising’ fibrin clot structure may be of benefit in the prevention and treatment of cardiovascular disease.
Keywords: Fibrin; fibrinogen; clot structure; cardiovascular disease